2021
DOI: 10.1002/hep.31488
|View full text |Cite
|
Sign up to set email alerts
|

A Fibrosis‐Independent Hepatic Transcriptomic Signature Identifies Drivers of Disease Progression in Primary Sclerosing Cholangitis

Abstract: Primary sclerosing cholangitis (PSC) is a heterogeneous cholangiopathy characterized by progressive biliary fibrosis. RNA sequencing (RNA-Seq) of liver tissue from PSC patients (n=74) enrolled in a 96-week clinical trial was performed to identify associations between biological pathways that were independent of fibrosis and clinical events. The effect of fibrosis was subtracted from gene expression using a novel computational approach. The fibrosis-adjusted gene expression patterns were associated with time to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…The UPR decreases ER stress and restores cellular homeostasis, and dysregulation of the UPR has been associated with several liver diseases. Notably, adult patients with the cholestatic liver disease PSC who have downregulation of ATF6 expression are at increased risk for more rapid disease progression and clinical complications 22 . Additionally, the IRE1α/XBP1 pathway has been studied in adult liver disease progression as well as murine models of ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…The UPR decreases ER stress and restores cellular homeostasis, and dysregulation of the UPR has been associated with several liver diseases. Notably, adult patients with the cholestatic liver disease PSC who have downregulation of ATF6 expression are at increased risk for more rapid disease progression and clinical complications 22 . Additionally, the IRE1α/XBP1 pathway has been studied in adult liver disease progression as well as murine models of ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the enhanced hepatic XBP1 pathway is protective in FXR deficient mice, which is consistent with the known adaptive and protective role of XBP1 in reducing or resolving ER stress. A recent transcriptome study using liver biopsies from PSC patients demonstrated that the expression of UPR genes was lower in the group of patients who were at increased risk for adverse PSC-related clinical events (15). Furthermore, we have shown in murine models that weanling mice are unable to adequately activate the hepatic XBP1 and other UPR pathways in response to bile acid or pharmacologically-induced ER stress, and this inadequate hepatic XBP1 activation causes increased liver injury and apoptosis (30).…”
Section: Discussionmentioning
confidence: 99%
“…Pathway analysis demonstrated increased expression of the liver UPR pathways in the NR:HBR group compared to the NR:Mild group. It has been previously reported that selected UPR genes are down-regulated in PSC patients with a high risk of developing PSC-related complications (7). Patients with progressive NASH also have UPR dysregulation and an attenuated UPR response compared to patients with benign hepatic steatosis (24), although this was not seen in other patient populations (25).…”
Section: Discussionmentioning
confidence: 99%
“…The hepatic UPR is important in the pathogenesis of many liver diseases including viral hepatitis, non-alcoholic fatty liver disease, alpha-1 antitrypsin deficiency, alcoholic liver disease and ischemia-reperfusion injury (9-11). Finally, in a recent study of PSC patients, differential expression of UPR genes was identified in patients who were at high risk for liver-related complications (7). Unfortunately, the role of the UPR in human cholestasis and cholestatic liver injury remains poorly understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation